Unprecedented Diversity of Lactococcal Group 936 Bacteriophages Revealed by Amplicon Sequencing of the Portal Protein Gene - Frantzen, Cyril Alexander (Viruses, 2019)
Lactococcus lactis is one of the most important bacteria in dairy fermentations, being used in the production of cheese and buttermilk. The processes are vulnerable to phage attacks, and undefined mixtures of lactococcal strains are often used to reduce the risk of bacteriophage caused fermentation failure. Other preventive measures include culture rotation to prevent phage build-up and phage monitoring. Phage diversity, rather than quantity, is the largest threat to fermentations using undefined mixed starter cultures. We have developed a method for culture independent diversity analysis of lytic bacteriophages of the 936 group, the phages most commonly found in dairies. Using, as a target, a highly variable region of the portal protein gene, we demonstrate an unprecedented diversity and the presence of new 936 phages in samples taken from cheese production. The method should be useful to the dairy industry and starter culture manufacturers in their efforts to reduce phage problems.